A method for assessing wheel fatigue reliability considering multiaxial stress state. (January 2020) - Yang, Liuqing; Hu, Ming; Zhao, Deming; Yang, Jing; Zhou, Xun
Electric multiple unit is a modern transportation tool with high efficiency and large carrying capacity. Regarding its high speed, reliability requirement of the train is very important. As the main load bearing component of a train, the wheel is subjected to harsh working condition. Rolling contact between wheel and rail leads to wheel fatigue failure so that the fatigue reliability of wheel becomes one of the most attractive fields in electric multiple unit reliability study. This article proposed a fatigue reliability assessment method. It could obtain critical parts' stress distribution efficiently through the force–stress relationship received by numerical simulation, so that it could assess wheel fatigue reliability under measured force–time spectrum. Also, multiaxial fatigue is considered in the method and the equivalent stress can be obtained by multiaxial model and fatigue experiment. Result of the case study shows that fatigue reliability of China Railway High-speed 5 wheel at 60, 000 km mileage is 68%.